2007
DOI: 10.1111/j.1471-4159.2007.05058.x
|View full text |Cite
|
Sign up to set email alerts
|

Dimemorfan protects rats against ischemic stroke through activation of sigma‐1 receptor‐mediated mechanisms by decreasing glutamate accumulation

Abstract: phosphate buffer; RMCA, right middle cerebral artery; RNS, reactive nitrogen species; ROS, reactive oxygen species; STAT-1, signal transducer and activator of transcription-1; TNF, tumor necrosis factor. AbstractDimemorfan, an antitussive and a sigma-1 (r 1 ) receptor agonist, has been reported to display neuroprotective properties. We set up an animal model of ischemic stroke injury by inducing cerebral ischemia (for 1 h) followed by reperfusion (for 24 h) (CI/R) in rats to examine the protective effects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 52 publications
(70 reference statements)
1
56
0
Order By: Relevance
“…In addition, colocalization of nitrotyrosine-and cleaved caspase-3-positive cells markedly increased in the ischemic cortex at 24 h of reperfusion; however, it was suppressed by FA treatment in the S-FA and R-FA groups. These results are consistent with previous reports which demonstrated that nNOS and iNOS expression are markedly increased in the ischemic area 24 h after cerebral ischemia, and pharmacologically-selective inhibitors of the glutamate receptor-PSD-95-nNOS complex and iNOS reduce nitrotyrosine formation, attenuate caspase-3 activation, and ameliorate ischemic brain injury [6,[20][21][22] . On the basis of these findings, we posit that FA exerts its protective effect against PSD-95, nNOS, and iNOS-mediated oxidative/ nitrative stress (nitrotyrosine) in the ischemic cortex of the S-FA and R-FA groups at 24 h of reperfusion, and the antioxidative/nitrative effect of FA further contributes to the inhibition of caspase-3-dependent apoptosis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, colocalization of nitrotyrosine-and cleaved caspase-3-positive cells markedly increased in the ischemic cortex at 24 h of reperfusion; however, it was suppressed by FA treatment in the S-FA and R-FA groups. These results are consistent with previous reports which demonstrated that nNOS and iNOS expression are markedly increased in the ischemic area 24 h after cerebral ischemia, and pharmacologically-selective inhibitors of the glutamate receptor-PSD-95-nNOS complex and iNOS reduce nitrotyrosine formation, attenuate caspase-3 activation, and ameliorate ischemic brain injury [6,[20][21][22] . On the basis of these findings, we posit that FA exerts its protective effect against PSD-95, nNOS, and iNOS-mediated oxidative/ nitrative stress (nitrotyrosine) in the ischemic cortex of the S-FA and R-FA groups at 24 h of reperfusion, and the antioxidative/nitrative effect of FA further contributes to the inhibition of caspase-3-dependent apoptosis.…”
Section: Discussionsupporting
confidence: 82%
“…Excitotoxicity induced by activation of glutamate receptors is the predominant mechanism underlying neuronal apoptosis in stroke [4] . Cerebral ischemic damage is associated with excessive release of excitatory glutamate, which subsequently upregulates not only the expression of neuronal nitric oxide synthase (nNOS), but also inducible nitric oxide synthase (iNOS) [5,6] . Numerous studies [7][8][9][10] have shown that the glutamate receptor-postsynaptic density-95 (PSD-95)-nNOS complex and iNOS produce an excessive amount of nitric oxide (NO) during cerebral I/R injury; NO immediately reacts with superoxide radicals to form peroxynitrite, which subsequently nitrates protein tyrosine residues, generating nitrotyrosine and leading to oxidative/nitrative stress.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that "excitotoxicity" is the major pathophysiological mechanism underlying ischemic stroke-induced brain injury. In such cases, excessive glutamate accumulation in the extracellular space causes an inappropriate activation of ionotropic N-methyl-daspartate (NMDA) receptors in the brain as a result of stroke onset (Lo et al, 2003;Shen et al, 2008). This excessive amount of glutamate stimulates neuron death through oxidative and/or nitrosative stresses that induce overproduction of reactive oxygen species (ROS), such as hydroxyl radicals (OH − ), superoxide anions (O 2 •− ) and hydrogen peroxide (H 2 O 2 ), or reactive nitrogen species (RNS) such as nitric oxide (NO • ) and peroxynitrite (OONO − ) (Shen et al, 2005(Shen et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Rats subjected to transient MCAO had reduced infarct volume when various sigma ligands such as dimemorphan [113], (+)pentazosin [114], and 4-phenyl-1-(4-phenylbutyl) piperidine [115] were administered during reperfusion. Inhibition of various components of the early response to stroke, such as NMDA receptor activation, neuronal nitric oxide synthesis, and inducible nitric oxide synthesis have been postulated to mediate this neuroprotection.…”
Section: Therapeutic Targets For Stroke At Delayed Timepointsmentioning
confidence: 99%